Validation of Circular RNAs Using RT‐qPCR After Effective Removal of Linear RNAs by Ribonuclease R. Issue 7 (7th July 2021) - Vromman, Marieke; Yigit, Nurten; Verniers, Kimberly; Lefever, Steve; Vandesompele, Jo; Volders, Pieter‐Jan
Abstract: Circular RNAs (circRNAs) are a class of endogenous noncoding RNAs that have been shown to play a role in normal development, homeostasis, and disease, including cancer. CircRNAs are formed through a process called back‐splicing, which results in a covalently closed loop with a nonlinear back‐spliced junction (BSJ). In general, circRNA BSJs are predicted in RNA sequencing data using one of numerous circRNA detection algorithms. Selected circRNAs are then typically validated using an orthogonal method such as reverse transcription quantitative PCR (RT‐qPCR) with circRNA‐specific primers. However, linear transcripts originating from endogenous trans‐splicing can lead to false‐positive signals both in RNA sequencing and in RT‐qPCR experiments. Therefore, it is essential to perform the RT‐qPCR validation step only after linear RNAs have been degraded using an exonuclease such as ribonuclease R (RNase R). Several RNase R protocols are available for circRNA detection using RNA sequencing or RT‐qPCR. These protocols—which vary in enzyme concentration, RNA input amount, incubation times, and cleanup steps—typically lack a detailed validated standard protocol and fail to provide a range of conditions that deliver accurate results. As such, some protocols use RNase R concentrations that are too high, resulting in partial degradation of the target circRNAs. Here, we describe an optimized workflow for circRNA validation, combining RNase R treatment and RT‐qPCR. First, we outline the steps for circRNA primer design and qPCR assay validation. Then, we describe RNase R treatment of total RNA and, importantly, a subsequent essential buffer cleanup step. Lastly, we outline the steps to perform the RT‐qPCR and discuss the downstream data analyses. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : CircRNA primer design and qPCR assay validation Basic Protocol 2 : RNase R treatment, cleanup, and RT‐qPCR